Student-led discussions of landmark discovery articles: a foothold in teaching primary virology literature - Camilla E. Hippee; Aloysius Klingelhutz; Li Wu (Journal of Microbiology & Biology Education)
ABSTRACT Introducing students to primary scientific literature is essential for establishing scientific literacy; however, students can feel overwhelmed by the amount of information within a research article. In our virology discussion courses, we address this issue by creating a student-centered and active learning environment. Students present and guide discussions on the rationales, background, methods, results, and conclusions from research literature in class. This approach has been applied in both undergraduate and graduate settings for students studying microbiology, with different expectations and criteria between the two groups. Student evaluations collected from three semesters were positive toward the teaching methods. Students praised the inclusion of “landmark discovery” articles, which examined paradigm-shifting concepts in virology. Undergraduates expressed their increased confidence in comprehending scientific literature and highlighted the impact of group work. In a critique of the course, students suggested more variety in the topics covered and inclusion of recent publications. Overall, our enhanced approach and methods improved student experiences with primary scientific literature and promoted student learning.